2008
DOI: 10.1108/13552510810877647
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and success factors for overcoming challenges in TPM implementation in Indian manufacturing industry

Abstract: PurposeThe purpose of this study is to evaluate the challenges before Indian manufacturing organizations for adapting to proactive total productive maintenance (TPM) initiatives. The aim of this research is to critically examine the factors influencing the implementation of TPM practices in the Indian manufacturing industry, and to devise an overall maintenance strategy for overcoming obstacles to successful TPM implementation.Design/methodology/approachThe study focuses on systematic identification of obstacl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
17

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 32 publications
(39 reference statements)
2
81
1
17
Order By: Relevance
“…If employees are aware of the processes and have been taken into confidence, they would show a responsible attitude towards the implementation of these processes, which would help achieve the implementation of objectives as well. A similar viewpoint was also expressed by Ahuja and Khamba (2008b), Kumar et al (2014) and Eswaramoorthi et al (2011) that if employees are provided with detailed knowledge and training regarding many techniques such as (5S and TPM), and are made aware of the benefits they can bring to themselves as well as to the company, the employees will put in more effort and time to make the implementation of these techniques a success. Finally, Gapp et al (2008) suggested that successful implementation of 5S and TPM would require continuous organizational resolve for their implementation.…”
Section: Awareness and Sense Of Responsibilitymentioning
confidence: 96%
See 4 more Smart Citations
“…If employees are aware of the processes and have been taken into confidence, they would show a responsible attitude towards the implementation of these processes, which would help achieve the implementation of objectives as well. A similar viewpoint was also expressed by Ahuja and Khamba (2008b), Kumar et al (2014) and Eswaramoorthi et al (2011) that if employees are provided with detailed knowledge and training regarding many techniques such as (5S and TPM), and are made aware of the benefits they can bring to themselves as well as to the company, the employees will put in more effort and time to make the implementation of these techniques a success. Finally, Gapp et al (2008) suggested that successful implementation of 5S and TPM would require continuous organizational resolve for their implementation.…”
Section: Awareness and Sense Of Responsibilitymentioning
confidence: 96%
“…Therefore, Jadhav et al (2014) and Haddad & Jaaron (2012) highlighted, that the major roadblock in the successful implementation of techniques that lead to improving production effectiveness is the reluctance of management to empower employees. Ahuja & Khamba (2008b) also shared the same viewpoint that the rigid bureaucratic structures of the organizations are that impedes empowerment of the employees. Furthermore, there are the other researchers were of the view that employees are the major cornerstone in the implementation of many techniques such as 5S, Kaizen, Six Sigma and TPM that could enhance the efficiency of an organization and its competitiveness, and without their involvement in the process of the implementation, would render these techniques ineffective during their implementation (Ahuja & Khamba, 2008b;Haroun & Duffuaa, 2009;Rolfsen & Langeland, 2012).…”
Section: Manager-subordinate Relationship (Empowerment/autonomy)mentioning
confidence: 98%
See 3 more Smart Citations